Measurement of Electron Neutrino Quasielastic and Quasielasticlike Scattering on Hydrocarbon at < E-v >=3.6 GeV - Wolcott, J (2016)
CONCYTEC, DGI-PUCP, and IDI/IGI-UNI (Peru), by Latin American Center for Physics (CLAF), and by RAS and the Russian Ministry of Education and Science (Russia). We thank the MINOS Collaboration for use of its near detector data. We acknowledge the dedicated work of the Fermilab staff responsible for the operation and maintenance of the beam line and detector.